1998
DOI: 10.2214/ajr.171.3.9725302
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic sonography of HIV-associated nephropathy: new observations and clinical correlation.

Abstract: OBJECTIVE. HIV-associatednephropathyis an important causeof morbidity that is characterized clinically by uremia and proteinuria and histologically by focal segmental glomerulosclerosis. In the largestseriesyet analyzed to our knowledge,we describenew sonographic findings and record the prevalence of other findings. We review the sonographic findings in a large group of HIV-infected patients. MATERIALS AND METHODS. Seventy-sixconsecutiveHIV-infected patientsunderwent renal sonography. Abnormalities seen on son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 3 publications
4
13
0
1
Order By: Relevance
“…Fibro-cavitations were similarly noted in other previous studies in Africa and particularly Uganda (Nimfa, 2002;Sharma, 2007;Di Fiori, 1998;Chaisson, 1987;Eriki, 1991). Therefore, significant burden of HIV-related tuberculosis was probably due to reactivation of the latent infection and progression of chronic disease as a result of immunodeficiency (table 2).…”
Section: Discussionsupporting
confidence: 78%
“…Fibro-cavitations were similarly noted in other previous studies in Africa and particularly Uganda (Nimfa, 2002;Sharma, 2007;Di Fiori, 1998;Chaisson, 1987;Eriki, 1991). Therefore, significant burden of HIV-related tuberculosis was probably due to reactivation of the latent infection and progression of chronic disease as a result of immunodeficiency (table 2).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, a highly echogenic cortex has been shown to be the most common abnormality in patients with parenchymal renal diseases and patients with HIV-related renal disorders. 3,8 Nonetheless, earlier studies have shown no correlation between the nature and severity of the glomerular lesion on renal biopsy and the sonographic findings. [9][10][11][12] Paivansalo et al 8 observed that, although an echogenic cortex was slightly more frequent in tubulointerstitial diseases than in the glomerular ones, no specific sonographic Insuff obs indicates insufficient observations.…”
Section: D a Bmentioning
confidence: 97%
“…There is a misconception among uninformed radiologists and nephrologists that enlarged kidneys are a consistent finding in HIV-positive patients, but that has been dismissed by several prior studies. 2,3 This perception is based on published case reports and nephrology textbook citations. 15 In a study by Di Fiori et al 3 in which sonographic findings in a large group of HIVinfected patients were reviewed, only 20% of 152 kidneys imaged were enlarged.…”
Section: D a Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic findings are of a black patient with relatively late stage HIV disease presenting with proteinuria (>1 g/24 hours), rising serum creatinine, and enlarged echogenic kidneys on ultrasound. 26 Other causes of renal failure (table 1) should be excluded (table 2) 34 and a renal biopsy will be necessary in cases not typical of HIVAN (table 2) or in patients failing to respond to therapy which includes HAART.…”
Section: Diagnosismentioning
confidence: 99%